Bacterial Consortia as a Suitable Innovation for Management of Agriculture Solid Waste - Kannan, R.; Kallapiran, K. Ajay (Emerging Issues in Agricultural Sciences Vol. 3, 2023)
Native bacterial microflora from old dumping yards will enhance the agriculture solid waste management and under stress environment particular bacterial consortia will produce a variety of enzymes such as protease, lipase, and amylase. The majority of agricultural waste is made up of residues like cellulose, lignin, chitin, keratin, and pectin, which can only be broken down by naturally occurring bacteria, fungi, protozoa, and actinomycetes that are capable of doing the job. In addition, microbes are important in the breakdown of various agricultural wastes. Agriculture wastes are swiftly handled by efficient native bacteria that generate eco-friendly, affordable dynamic substrates from the field itself and construct compost beds above ground level to prevent environmental damage. At intervals of four days, consortium native bacterial cultures are added to the beds while the temperature and moisture are held constant. After 28 days, the material breakdown converts into compost, and this final microbial compost is added to the vermicomposting process to produce vermicompost. The usage of bacteria can have favorable long-term environmental effects on the ecosystem.